2021
DOI: 10.1080/11101849.2021.1930401
|View full text |Cite
|
Sign up to set email alerts
|

Driving pressure-guided ventilation versus protective lung ventilation in ARDS patients: A prospective randomized controlled study

Abstract: Background: Secondary analyses of randomized controlled trials found that driving pressure (DP) ≤ 14 cm H 2 O may be associated with improved clinical outcomes in acute respiratory distress syndrome (ARDS) patients. Therefore, the aim of this study was to evaluate the effect of DP-guided ventilation compared to conventional protective lung ventilation (PLV) on clinical outcomes in ARDS patients. Methods: In this prospective, controlled trial, 110 patients with ARDS were randomly assigned according to ventilato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…There were significant differences in DP between weaning success and weaning failure and between alive and dead. This is in line with Hamama et al who reported that, the reduced rate of mortality may be attributed to the use of DP guided ventilation for patients with ARDS (17) . The retrospective analysis of several studies in patients with ARDS comparing different PEEP levels at the same VT or different VT levels at the same PEEP, or a combination of both, suggested that DP (the difference between Pplat and PEEP) was a strong predictor of mortality as compared with low VT and Ppl.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There were significant differences in DP between weaning success and weaning failure and between alive and dead. This is in line with Hamama et al who reported that, the reduced rate of mortality may be attributed to the use of DP guided ventilation for patients with ARDS (17) . The retrospective analysis of several studies in patients with ARDS comparing different PEEP levels at the same VT or different VT levels at the same PEEP, or a combination of both, suggested that DP (the difference between Pplat and PEEP) was a strong predictor of mortality as compared with low VT and Ppl.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, pneumothorax was occurred in 6 patients (9.4%) while pleural effusion was occurred in 5 patients (7.8%). Other studies such as the study of Hamama et al (17) . Cavalcanti et al (20) explained complication by alveolar overdistention and pneumothorax produced by unnecessary higher PEEP.…”
Section: Discussionmentioning
confidence: 99%